Efficiency, energy and economic analysis of twisted tape inserts in a thermosyphon solar flat plate collector with Cu nanofluids - Sundar, L. Syam (2020)
Heat transfer, friction factor and efficiency of a thermosyphon type flat plate collector with and without twisted tape inserts were analyzed experimentally. Water based Cu nanofluids were used as the absorber fluid to receive the heat from solar radiation into the flat plate collector. The experiments were conducted for volume concentrations of 0.1% and 0.3% and twist ratios of H/D = 5, 10 and 15. Results reveal that the heat transfer rate and efficiency of nanofluids increase with the increase of particle volume concentrations. The Nusselt number of 0.3% nanofluid is enhanced up to 20.46%, and it is further enhanced up to 46.90% with twisted tape insert of H/D = 5 with a maximum friction factor penalty of 1.477-times compared to plain collector. The efficiency of the solar collector with water is 52% and it is enhanced to 58% for 0.3% nanofluid, whereas it is further enhanced to 64% for 0.3% nanofluid with twisted tape insert of H/D = 5. Empirical correlations are proposed based on the experimental data for the friction factor and Nusselt number with a standard deviation of less than ±6.5%. The study indicates that for 100 units of solar flat plate collector the use of 0.1% and 0.3% Cu nanofluids leads to weight savings of 284 kg and 567 kg, respectively. The total weight of 100 units of solar flat plate collector is further saved by 767 kg, 1050 kg and 1250 kg for 0.3% nanofluid with twisted tape inserts of H/D = 15, H/D = 10 and H/D = 5, respectively. The collector cost is reduced by 5.66% and 11.33% for 0.1% and 0.3% nanofluids, and it is further reduced to 25% for 0.3% nanofluid with a twisted tape insert of H/D = 5.